2020
DOI: 10.1007/s11042-020-09313-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in assistive ambient living technologies for ageing well

Abstract: Assistive Ambient Living (AAL) in ageing refers to any device used to support ageing related psychological and physical changes aimed at improving seniors’ quality of life and reducing caregivers’ burdens. The diffusion of these devices opens the ethical issues related to their use in the human personal space. This is particularly relevant when AAL technologies are devoted to the ageing population that exhibits special bio-psycho-social aspects and needs. In spite of this, relatively little research has focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…After daily use, the older adults might have realized that the content of ECAs' dialogues was not as extensive, smart and personal as they expected. Little personalization and inferior or stigmatized content seen as a threat to their autonomy, might have affected the older adults' satisfaction with the ECAs Panico et al, 2020;Troncone et al, 2020). Since the amount and the content of dialogues differed across the ECAs, this adaptation gap might have been larger for some ECAs than for others, which might have affected our results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…After daily use, the older adults might have realized that the content of ECAs' dialogues was not as extensive, smart and personal as they expected. Little personalization and inferior or stigmatized content seen as a threat to their autonomy, might have affected the older adults' satisfaction with the ECAs Panico et al, 2020;Troncone et al, 2020). Since the amount and the content of dialogues differed across the ECAs, this adaptation gap might have been larger for some ECAs than for others, which might have affected our results.…”
Section: Discussionmentioning
confidence: 94%
“…But, how do we design ECAs in a multi-agent eHealth application for older adults? Research on the design of eHealth applications for older adults in general teaches us that personalization of the applications is an important factor in older adults' acceptance of the applications Panico et al, 2020). Heerink et al shows that this also applies to ECAs: perceived adaptiveness affects older adults' acceptance of assistive social agent technology.…”
Section: Introductionmentioning
confidence: 99%
“…As a method for designing and implementing AAL facilities, the person-centered process has been found to be the best design methodology, as it allows for conversations between participants and healthcare professionals [78]. However, [19] found that highly developed algorithms were needed to integrate more general cognitive aspects in the robot to enable it to diagnose certain illnesses, such as ASD.…”
Section: Discussionmentioning
confidence: 99%
“…We found some ethical principles applied to the design of social robot applications in healthcare, such as autonomy, beneficence, non-maleficence, fidelity, justice, utility, and independence [78]. The same authors noted certain ethical requirements in artificial intelligence algorithms for AAL and social robots, like (1) human agency, (2) robustness, (3) privacy, (4) transparency, (5) non-discrimination, (6) wellbeing, and (7) accountability to account for the negative impacts of the systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation